Carbazole&benzoindole-based purely organic phosphors: a comprehensive phosphorescence mechanism, tunable lifetime and an advanced encryption system. Issue 40 (1st October 2021) - Qian, Chen; Ma, Zhimin; Yang, Bingxin; Li, Xianjiang; Sun, Jiayao; Li, Zewei; Jiang, Hong; Chen, Mingxing; Jia, Xinru; Ma, Zhiyong
Abstract : The same molecule synthesized from different carbazoles may show various properties, which originate from the trace isomer in purchased carbazole. By changing the content of isomers, the phosphorescence lifetime can be quantitatively adjusted. Abstract : The effect of carbazole isomers (benzoindole, Bd) on phosphorescence has attracted much research interest recently since it was discovered last year. However, the phosphorescence mechanism of carbazole/benzoindole is still unclear and urgently needs to be addressed. Where is the true crystallization phosphorescence in pure carbazole-based systems? What can we do to make full use of the isomer effect? In order to distinguish the crystallization phosphorescence from the isomer induced phosphorescence, we introduced halogens to the PhCz skeleton to gain intense crystallization phosphorescence, and synthesized the target molecules with carbazole from different sources. The target molecule synthesized from the purchased carbazole (CNCZBr-Cm) depicts a bright yellow afterglow (550 nm) with ultralong lifetime at room temperature, whereas the same molecule synthesized from synthesized carbazole (CNCZBr-Lab) only shows bright green phosphorescence at 500 nm and its phosphorescence is short-lived, which is verified to be the true crystallization phosphorescence. HPLC-HRMS spectroscopy showed the isomer in CNCZBr-Cm and determined its content to be as low as 0.024%. The carbazole isomers help to form a charge separated state, which reduces the radiation rate of phosphorescence, leading to an ultralong afterglow. We propose a more comprehensive phosphorescence mechanism for the carbazole&benzoindole system, including molecular phosphorescence (453 nm) and carbazole crystallization/dimer phosphorescence (500 nm), and carbazole&benzoindole heterojunction phosphorescence (550 nm). Furthermore, by adjusting the ratio of isomers, a series of doped systems with different phosphorescence lifetimes and intensities can be obtained. The proposed mechanism inspired us to obtain a simple but universal strategy for quantitatively adjusting the lifetime of carbazole-based phosphors and the obtained materials can be put into practical applications in the advanced encryption field.